2020
DOI: 10.3390/jmse8080559
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Potential in the Animal Feed: A Review

Abstract: Seaweed (known as marine algae) has a tradition of being part of the animal feed in the coastal areas, from ancient times. Seaweeds, are mixed with animal feed, because when consumed alone can have negative impact on animals. Thus, seaweeds are very rich in useful metabolites (pigments, carotenoids, phlorotannins, polyunsaturated fatty acids, agar, alginate and carrageenan) and minerals (iodine, zinc, sodium, calcium, manganese, iron, selenium), being considered as a natural source of additives that can substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
160
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(167 citation statements)
references
References 118 publications
(207 reference statements)
3
160
0
4
Order By: Relevance
“…The present data showed that ADG tended to be higher in rabbit fed the natural mixture and the feed conversion ratio was enhanced in rabbit fed the dietary supplement, suggesting a better feed conversion due to the probiotic, antibacterial and antioxidant effects of the natural mixture used [ 11 ]. An enhancement of nutrient digestibility was also observed in several animal species fed seaweed [ 12 ]. The present data are in line with studies in rabbit showing that natural extract dietary supplementation positively affected rabbit’s growth performances [ 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data showed that ADG tended to be higher in rabbit fed the natural mixture and the feed conversion ratio was enhanced in rabbit fed the dietary supplement, suggesting a better feed conversion due to the probiotic, antibacterial and antioxidant effects of the natural mixture used [ 11 ]. An enhancement of nutrient digestibility was also observed in several animal species fed seaweed [ 12 ]. The present data are in line with studies in rabbit showing that natural extract dietary supplementation positively affected rabbit’s growth performances [ 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that dietary brown seaweeds in livestock had a positive effect on health, growth performance, and meat quality due to their nutraceuticals properties and content of sulfated polysaccharides, phlorotannins, diterpenes, omega-3 polyunsaturated fatty acids, minerals and vitamins [ 11 , 12 ]. Moreover, brown seaweeds represent a renewable and sustainable feed ingredient for their high productivity if compared to other conventional ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to terrestrial higher plants, seaweed polysaccharides have some similar structural features (4-linked glucan, mannan and xylan) but are unique in the linkage structure of carrageenans, agarans, porphyrans, alginates, fucoidans, ulvans, 1,3-β-D-xylan, mixed linkage xylan, and glucuronans [ 121 , 122 ]. Despite this structural complexity, seaweed polysaccharides with various structural features can be hydrolysed by carbohydrate-active enzymes (CAZyme) encoded within the genomes of gut microbiota (e.g., Bacteroides) during anaerobic fermentation [ 72 ].…”
Section: Seaweed Bioactives and Ch 4 Emissions mentioning
confidence: 99%
“…The rumen microbiota can also adapt to metabolise seaweed polysaccharides. Recently, there has been increasing interest in the use of seaweeds for livestock feed, and the restricted bioavailability of structurally complex seaweed polysaccharides can result in low CH 4 production [ 122 ].…”
Section: Seaweed Bioactives and Ch 4 Emissions mentioning
confidence: 99%
“…It was reported by Moury et al [45] that supplementation of Spirulina platensis in broiler diets may completely replace the incorporation of vitamin-mineral premix. Moreover, it can be substitute the antibiotic usage in animals [46].…”
Section: Algaementioning
confidence: 99%